PP-029 Development of ready-to-use adrenaline syringes for emergency use. (24th February 2014) - Fleury Souverain, S; Sigrist, T; Gschwind, L; Bouchoud, L; Sadeghipour, F; Bonnabry, P
Abstract : Background: Adrenaline (epinephrine) is commonly used in cardiac arrest, bronchospasm and anaphylaxis. To make the process safer and reduce the preparation time in wards in case of emergency, the availability of a ready-to-use form would be very welcome. Purpose: To develop a ready-to-use adrenaline syringe with a long shelf-life at room temperature stored in every resuscitation trolley of the hospital. Materials and methods: A capillary electrophoresis method with UV detection was developed and validated as stability-indicating method. An adrenaline tartrate solution (1 mg/mL) containing 5 mg/mL of sodium metabisulfite in 0.9% sodium chloride was filled under nitrogen flow and aseptic conditions into 5 mL polypropylene syringes (multipack of PlastiPak Becton Dickinson, NJ. USA). Stability was tested on syringes stored at 25°C for 1 year and analyses were performed at t = 0, 1, 3, 6, 9 and 12 months. The pH and non-visible particulate matter were measured throughout the study. Sterility was checked at the beginning and the end of the study. Results: Complete separation of adrenaline and its main degradation products was achieved in less than 10 min. An optimal period of 9 months at 25°C was defined to stock adrenaline syringes without loss in potency. After this length of storage, adrenaline content was 94% of the initial concentration (at t = 0) and the solution was colourless. At t = 12 months the concentration of adrenaline was still superior to 90% but the solution became yellow. The pH values did not change appreciably and the syringe content remained sterile throughout the study. Each syringe fulfilled all European Pharmacopoeia criteria in terms of non-visible particles. Conclusions: Adrenaline syringes 5 mg = 5 mL supplied by the hospital pharmacy were found to be stable for 9 months at 25°C. This ready-to-use preparation stored in resuscitation trolleys should contribute to an improved safety of adrenaline use in case of emergency. No conflict of interest.